A Computational Study on the Hydride Transfer Mechanism between Nicotinamide and Menadione. Issue 42 (14th November 2018) - Rezazadeh, Shiva; Ebrahimi, Ali
Abstract: Menadione (MD) or vitamin K3 is a component of multivitamin drugs, which exhibits a wide range of pharmacological eﬀects relevant to human health. Nicotinamide adenine dinucleotide (NAD) catalyzes the oxidation process of MD through hydride transfer from nicotinamide (NA) to MD. In the present study, the hydride transfer mechanism between NA and MD was investigated using the quantum mechanical calculations at the M06‐2X/6‐31G (d, p) level of theory in the gas‐phase and solution media. Two mechanisms were proposed to clarify the cyclic redox of MD via NA: one includes direct hydride transfer (DHT) in one step and other includes single electron and proton transfer (SET‐PT) in two steps through an intermediate. Although the energy barrier is almost equal on two pathways, the results of natural bond orbital (NBO), and the molecular electrostatic potential (MEP) are clearly in agreement with the SET‐PT mechanism, which is preferred to the DHT mechanism for hydride transfer from NA to MD. The cation and anion radicals of NA and MD facilitate the proton transfer from NA to MD in the SET‐PT pathway. In addition, the binding energy between NA and MD and the energy barrier of proton transfer increase by the electron‐withdrawing substituents (EWSs) and decrease by electron‐donating substituents (EDSs) located at the C3 position of NA. A higher binding energy makes the intermediate more stable, which is accompanied with the increase in the energy barrier of proton transfer step. Abstract : Two mechanisms were proposed to hydride transfer from nicotinamide (NA) to Menadione (MD): the first mechanism is direct hydride transfer (DHT), and the second is single electron and proton transfer (SET‐PT) through an intermediate. The results of this study suggest that the 1 SET‐PT mechanism is preferred over the DHT. The cation and anion radicals of NA and MD facilitate the proton transfer from NA to MD in the SET‐PT pathway.